Chemical Composition and Toxicity of the Essential Oil of Coriandrum sativum L. and Petroselinum crispum L. Against Three Stored-Product Insect Pests. Issue 8 (16th November 2016) - Maroufpoor, Mostafa; Ebadollahi, Asgar; Vafaee, Yavar; Badiee, Edris
Abstract: The utilization of natural and bio-rational insecticides such as plant essential oils has been extended in the recent years because of negative effects on environment and human health of synthetic chemicals. In the present study, toxicity of essential oils isolated from parsley, Petroselinum crispum L., and coriander, Coriandrum sativum L., have been investigated against three major stored-product insect pests; cowpea weevil (C allosobruchus maculates F.), Mediterranean flour moth ( Ephestia kuehniella Zeller) and Indian meal moth ( Plodia interpunctella (Hübner)). Chemical analysis by gas chromatography-mass spectrometry displayed Dlimonene (18.83 %), myristicin (17.18 %) and apiol (10.09 %) in the essential oil of P. crispum and (+)-(S)carvone (39.55 %) and 4-carene (35.28 %) in the C. sativum essential oil were main components. The essential oils revealed significant toxicity against tested insects. LC50 values of C. sativum and P. crispum essential oils against C. maculatus adults were 72.167 and 71.071 μ/l air, respectively. These values were achieved as 62.633 and 52.412 μ/l air for E. kuehniella and 50.956 and 55.197 μ/l air for P. interpunctella larvae, respectively. For both essential oils a correlation between concentrations and mortality percentage has been attained. According to the results of present study, essential oils of P. crispum and C. sativum have worthy potential in the integrated management of C. maculatus, E. kuehniella and P. interpunctella .